Determination of Interfacial Area in Gas-Liquid Two Phase by Light Transmission - Seied Hossein Ghiassi; Ali Akbar Safekordi; Fatemeh Babazadeh Shareh (Iranian Journal of Chemistry & Chemical Engineering, 2012)
The purpose of the present paper is to develop light beam method to measurement of interfacial area in a rectangular gas-liquid bubble column. Total interfacial area can be determined in bubble column filled by transparent liquid by light transmission method. According to pervious researches, the fraction of parallel light is function of interfacial area and optical path length that these two parameters imply Transmission Number or NT.The drop diameters were measured in the range of 2.2 to 5 mm, and in this range, the specific area is found to depend only upon the light transmission. Three different systems with various liquid phases have been used in this work.It had been proved that light transmission method for dilute suspension or stationary gas phase has a good consequence. In this work, good agreement between actual and calculated interfacial area proves that light transmission method would be able to determine interfacial area in multiple scattering, and it is possible to use earlier mathematic model to measure interfacial area in multiple scattering in gas-liquid bubble columns.